2023
DOI: 10.1615/critrevoncog.2023046835
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Therapies of Oral Cancers: Highlights on Chemotherapeutic Agents and Radiotherapy, Their Adverse Effects, and the Cost Burden of Conventional Therapies

Abstract: Oral cancer (OC) is increasing worldwide, and it is mostly present to clinic in the late-stage of disease. Cancer of the lips, tongue, hard palate, upper and lower gingiva, buccal mucosa, and retromolar trigone are all included in the category of oral cavity cancer. Disease symptomatology and pathological grading decides the course of treatment. Several treatment modalities either alone in combinations may be utilized for oral squamous cell carcinoma (OSCC), including surgery, radiotherapy (external beam radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Furthermore, in this study, it was observed that the average TL is similar between the different cancer stages, probably because the stage was a covariate, requiring a larger sample size of each stage to obtain decisive conclusions. Concerning systemic cancer treatment, it was found that there is greater TL in patients who underwent both treatments (chemotherapy and radiotherapy), possibly because these therapies affect bone tissue, bacterial balance and salivary glands ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study, it was observed that the average TL is similar between the different cancer stages, probably because the stage was a covariate, requiring a larger sample size of each stage to obtain decisive conclusions. Concerning systemic cancer treatment, it was found that there is greater TL in patients who underwent both treatments (chemotherapy and radiotherapy), possibly because these therapies affect bone tissue, bacterial balance and salivary glands ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prevention and treatment of cancer have become two of the most promising directions. At present, the main treatment for cancer is radiotherapy and chemotherapy [ 147 , 148 ], but these methods are harmful to the human body [ 149 ], and it is more realistic and reliable to prevent cancer through daily dietary intake.…”
Section: Discussionmentioning
confidence: 99%